Perlindungan Hukum Terhadap Wisatawan Menurut Undang-Undang Nomor 10 Tahun 2009 Tentang Kepariwisataan - Sheilla Kristiana Putri (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2023)
Tourism is a group of business fields that produce various services and goods needed by tourists who travel. In tourism, the protection of tourists is very important. Both for domestic and foreign tourists. As a tourist destination, Indonesia has an obligation to provide legal protection for tourists visiting this country. Therefore, Law Number 10 of 2009 concerning Tourism in Indonesia regulates legal protection for tourists. This paper discusses legal protection for tourists and legal remedies that can be taken by tourists if they experience losses due to consuming goods/services. The research method used is normative juridical research. Legal materials in the form of primary and secondary legal materials, this research was collected through literature study and analyzed using qualitative normative analysis techniques.